Analisis Dan Upaya Peningkatan Penilaian Kinerja Guru Di SDN Pikatan - ., Ryzca Siti Qomariyah; ., Azizah Tun Nafsiyah; ., Iwing Ade Miranda; ., Wulan Agustin (CV. ITTC INDONESIA, 2022)
The purpose of this study was to find out how teacher performance is evaluated and how the efforts of school principals improve teacher performance at SDN Pikatan, Gending District, Probolinggo Regency. This study uses a type of qualitative research method. Data collection techniques are interview techniques, observation and documentation. Data analysis in this study is data reduction, data presentation and conclusion. We guarantee the validity of the data in this study, namely credibility, transferability, reliability and verifiability. Performance evaluation is a supervisory activity in which employee performance is evaluated and policies are decided upon. The school principal seeks to improve the performance of teaching staff and provides opportunities or opportunities for each teacher to attend training courses, workshops and seminars. to improve the professional ability of teachers. This means that the madrasa head works with superiors to guide teachers and extracurriculars are held every year to improve the performance of teachers. Improving teacher performance is not just a principle, but teachers must also have the motivation to do better in the future. Determining teacher performance evaluation and the principal's efforts to improve teacher performance begins with planning, implementing, and evaluating the realization of teacher performance in the classroom. In addition, training courses, workshops and seminars are organized by schools and extracurricular institutions every year to increase teacher effectiveness.